Comparative study of individual and Co-Application of biochar and wood vinegar on blueberry fruit yield and nutritional quality. (May 2020) - Zhang, Yuchan; Wang, Xiao; Liu, Bingjie; Liu, Qiang; Zheng, Hao; You, Xiangwei; Sun, Ke; Luo, Xianxiang; Li, Fengmin
Abstract: Biochar and its by-product, wood vinegar, have attracted extensive attention owing to their great potentials in improving degraded soil, which is a global concern because of the threats to soil productivity and food security. However, the effect of biochar or wood vinegar on blueberry production is unknown. Therefore, a field trial was conducted to investigate the effects of individual and co-application of biochar (BC450) and wood vinegar (WV450) derived from blended wood waste on the blueberry tree ( Vaccinium corymbosum L.) growth, fruit yield, appearance, and nutritional quality as well as the soil properties and nutrient availability. Regardless of individual or co-application, all the amendments had little effect on tree growth. Although BC450 and WV450 increased the fruit yield, the differences between the amended treatments were non-significant. Both the amendments had little effect on the apparent fruit quality, but improved the nutritional quality has been improved (e.g., increased vitamin C and decreased titratable acidity). Additionally, the individual or co-application of BC450 and WV450 had little effect on soil properties (except for soil organic matter), but increased the soil nutrient availability (e.g., NH4 + -N, NO3 ⁻-N, and Mg). The enhancement in the nutritional quality of the blueberry fruit can be mainly attributed to the increased nutrient availability. This is the first preliminary study that demonstrates that the individual or co-application of biochar and wood vinegar can be a potential strategy for reclaiming degraded soil and enhancing blueberry production. Graphical abstract: Image 1 Highlights: Application of biochar and wood vinegar has little effect on blueberry tree growth. Application of biochar and wood vinegar has no effect on apparent fruit quality. Co-application of biochar and wood vinegar improves nutritional quality of fruit. Improved fruit nutritional quality is due to increased soil nutrient availability.